S-38-2: PREVENTION OF EXPERIMENTAL GENETIC HYPERTENSION - GENOMIC CLUES FROM THE KIDNEY. (January 2023) - Byars, Sean; Prestes, Priscilla; Suphapimol, Vara; Vries, Nathan De; Melo, Mariana Del Rosso Le; Maier, Michelle; Samani, Nilesh; Berka, Jennifer Wilkinson; Allen, Andrew; Charchar, Fadi; Harrap, Stephen
Abstract : Brief treatment with renin-angiotensin system (RAS) inhibitors permanently reduces the genetic hypertension of the spontaneously hypertensive rat (SHR). The kidney is involved in this reprogramming, but relevant molecular genetic changes are unknown. We studied SHR kidney RNA differential expression (controlling for non-specific effects of lower BP) and DNA methylation 6 weeks after treatment with the angiotensin receptor blocker losartan from 10 to 14 weeks of age. RNA sequencing revealed a significant 6-fold (P < 0.0001) increase in renin gene (Ren) expression during treatment. Six weeks later direct mean arterial pressure remained lower than untreated SHR (123 vs 140 mmHg, P = 0.001) and kidney Ren expression was reduced by 23% (P = 0.03) and DNA methylation within the Ren promoter region was significantly increased (P = 0.04). Experiments with the ACE inhibitor perindopril and renin immunohistochemical analyses confirmed significant long-term reduction in kidney Ren expression following RAS inhibition. Genomic RNA sequencing analysis identified 13 candidate genes (Grhl1, Ammecr1l, Hs6st1, Nfil3, Fam221a, Lmo4, Adamts1, Cish, Hif3a, Bcl6, Rad54l2, Adap1, Dok4) and the miRNA miR-145-3p that were significantly differentially expressed and correlated closely with decreased Ren expression. Ten of the candidates were central to gene networks that exhibited significant enrichment for genes relevant to BP and the RAS. We propose that reduced renin gene expression is a legacy of early RAS inhibition and responsible for the persistent reduction in BP in SHR.